TRACKING THE ROLE OF LEMBAGA ADAT TANA SAMAWA AS AN INFORMAL DEMOCRATIC INSTITUTION IN THE LOCAL POLITICAL ARENA IN SUMBAWA - Johan Wahyudi (Jurnal Ilmu Pemerintahan Widya Praja, 2024)
This study aims to explain how informal democratic institutions, such as aristocracy and customary institutions, interact with formal democratic institutions within the framework of modern state institutions. This study was conducted in the Sumbawa Regency by considering the Lembaga Adat Tana Samawa (Tana Samawa Customary Institution) which is the embodiment of the revitalization of the Sumbawa Sultanate as an informal democratic institution. This study aims to further trace how aristocracy in Sumbawa, represented by Tana Samawa Customary Institution (LATS), plays a role in local democracy. This study uses Helme and Levitsky's analytical framework to examine how informal institutions are positioned relative to formal institutions as seen in four typologies; (1) complementary informal institutions, (2) accommodating informal institutions, (3) competing informal institutions, and (4) substitutive informal institutions. By interviewing Sumbawa LATS administrators, Sumbawa regional leaders, and document studies, this research shows that LATS Sumbawa Regency can complement the role of formal institutions and accommodate formal institutions. Keywords; Informal Democracy, Formal Democracy, Lembaga Adat Tana Samawa (LATS), Sumbawa